Understanding the nature and threats of drug trafficking to national and regional security in West Africa1. Issue 1 (18th February 2014) - Aning, Kwesi; Pokoo, John
Several West African states are threatened by increasingly powerful transnational organised criminal networks. Yet, scholarly work on the nature, characteristics and strength of these groups and how their activities threaten states remains sparse, leading to misunderstandings and inadequate appreciation of the precise nature of the threats they pose to West Africa. This paper seeks to fill these lacunae in our knowledge. It focuses on the nexus between drugs, crime and terrorism. It argues that, the financial spin-offs from criminal activities contribute to the development of opportunistic relationships between criminals and extremist groups that threatens West Africa's fragile states. The analyses are based on evidence from several West African states, but employ the ongoing crisis in the Sahel, particularly Mali, as an empirical case, to demonstrate how 'profitable collusion' among different actors permits hollow states to become edifices that allows corruption, criminality and impunity to flourish.